Treatment Problems In Triple Negative Breast Cancer - Fasril , Thira; Hilbertina, Noza; Elliyanti, Aisyah (Jurnal Medis Islam Internasional, 2023)
Background: Breast cancer ranks second on the list of common diseases worldwide. It causes many deaths in the United States and Europe, second only to lung cancer. Triple-negative breast cancer (TNBC) does not express Estrogen Receptor (ER), Progesterone Receptor (PR), and Human Epithelial Receptor (HER2). It represents 24% of new cases of all breast cancer, and its incidence increases yearly. TNBC is a hormone-resistant breast cancer, so no current standard therapy exists. This article aims to explore regimen-resistant and troubleshooting treatment responses in TNBC cases. The method of writing this article is a literature review of studies using the keywords triple-negative breast cancer treatment and regimen, which are limited to only the most recent articles, 2012-2022, using search engines from PubMed, Science Direct, and Google Scholar. Results: There is no definitive therapy for the triple-negative breast cancer subtype, in which the TNBC type has no target receptor. Chemotherapy is the SOC of TNBC for early stage treatment. For late-stage and relapsed TNBC, however, chemotherapy is no longer the first choice. Currently there is no standard chemotherapy regimen that can be given to patients who experience relapse after chemotherapy because they will have a short response and lead to metastases. Some studies have shown that chemotherapy gives a better response, but the prognosis of TNBC remains poor. TNBC has different responses to therapy. TNBC showed a good response to combination chemotherapy along with pembrolizumab, capecitabine, olaparib, and radiotherapy, compared to chemotherapy by itself. Surgical therapy, such as Breast-Conserving Surgery (BCS), does not improve better prognosis in TNBC patients. Conclusions: Combining pembrolizumab, olaparib, capecitabine, and radiotherapy with chemotherapy increased survival rates compared to chemotherapy only.